Re‐evaluation of carrageenan (E 407) and processed Eucheuma seaweed (E 407a) as food additives. (26th April 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The present opinion deals with the re‐evaluation of the safety of food‐grade carrageenan (E 407) and processes Eucheuma seaweed (E 407a) used as food additives. Because of the structural similarities, the Panel concluded that processed Eucheuma seaweed can be included in the evaluation of food‐grade carrageenan. Poligeenan (average molecular weight 10–20 kDa) has not been authorised as a food additive and is not used in any food applications. In its evaluation of carrageenan (E 407) and processed Eucheuma seaweed (E 407a), the Panel noted that the ADME database was sufficient to conclude that carrageenan was not absorbed intact; in a subchronic toxicity study performed with carrageenan almost complying with the EU specification for E 407 in rats, the no‐observed‐adverse‐effect level (NOAEL) was 3, 400–3, 900 mg/kg body weight (bw) per day, the highest dose tested; no adverse effects have been detected in chronic toxicity studies with carrageenan in rats up to 7, 500 mg/kg bw per day, the highest dose tested; there was no concern with respect to the carcinogenicity of carrageenan; carrageenan and processed Eucheuma seaweed did not raise a concern with respect to genotoxicity; the NOAEL of sodium and calcium carrageenan for prenatal developmental dietary toxicity studies were the highest dose tested; the safety of processed Eucheuma seaweed was sufficiently covered by the toxicological evaluation of carrageenan; data were adequate for a refined exposure assessment for 41 out of 79 food categories. However, the Panel noted uncertainties as regards the chemistry, the exposure assessment and biological and toxicological data. Overall, taking into account the lack of adequate data to address these uncertainties, the Panel concluded that the existing group acceptable daily intake (ADI) for carrageenan (E 407) and processed Eucheuma seaweed (E 407a) of 75 mg/kg bw per day should be considered temporary, while the database should be improved within 5 years after publication of this opinion.